Congestion Control and Vehicle Ownership Restriction: The Choice of an Optimal Quota Policy - Koh, Winston T. H. (Institutional Knowledge at Singapore Management University, 2004)
Singapore introduced a vehicle quota system (VQS) in 1990 as part of its overall policy to control urban congestion. While the VQS has reduced the annual growth rate of the vehicle population to about 3 per cent, it has created uncertainty in the cost of vehicle ownership due to the fluctuations in licence prices. This paper discusses three issues relating to the optimal design of a VQS: licence transferability, sub-categorisation, and the choice of an auction format. The analysis shows that licence transferability is not unambiguously desirable, sub-categorisation is highly regressive, and an open auction format results in less aggressive bidding and lower licence prices.